Predicting IDH subtype of grade 4 astrocytoma and glioblastoma from tumor radiomic patterns extracted from multiparametric magnetic resonance images using a machine learning approach - Kandalgaonkar, Pashmina; Sahu, Arpita; Saju, Ann Christy; Joshi, Akanksha; Mahajan, Abhishek; Thakur, Meenakshi; Sahay, Ayushi; Epari, Sridhar; Sinha, Shwetabh; Dasgupta, Archya; Chatterjee, Abhishek; Shetty, Prakash; et al. (Frontiers in Oncology, 2022)
Background and Purpose: Semantic imaging features have been used for molecular subclassification of high-grade gliomas. Radiomics-based prediction of molecular subgroups has the potential to strategize and individualize therapy. Using MRI texture features, we propose to distinguish between IDH wild type and IDH mutant type high grade gliomas. Methods: Between 2013 and 2020, 100 patients were retrospectively analyzed for the radiomics study. Immunohistochemistry of the pathological specimen was used to initially identify patients for IDH mutant/wild phenotype and was then confirmed by sanger’s sequencing. Image texture analysis was performed on contrast-enhanced T1 (T1C) and T2 weighted (T2W) MR images. Manual segmentation was performed on MR image slices followed by single-slice multiple sampling image augmentation. Both whole tumor multislice segmentation and single-slice multiple sampling approach was used to arrive at the best model. Radiomic features were extracted which included first-order features, second-order (GLCM - Grey level co-occurrence matrix), and shape features. Feature enrichment was done using LASSO (Least Absolute Shrinkage and Selection Operator) regression followed by radiomic classification using Support Vector Machine (SVM) and a 10-fold cross-validation strategy for model development. The area under Receiver Operator Characteristic (ROC) curve and predictive accuracy were used as diagnostic metrics and evaluate the model to classify IDH mutant and wild-type subgroups. Results: Multislice analysis resulted in a better model compared to the single slice multiple sampling approach. 164 MR-based texture features were extracted, out of which LASSO regression identified 14 distinctive GLCM features for the endpoint which were used for further model development. The best model was achieved by using combined T1C and T2W MR Images using a Quadratic Support Vector Machine Classifier and a 10-fold internal cross-validation approach, which demonstrated a predictive accuracy of 89% with an AUC of 0.89 for each IDH mutant and IDH wild subgroups. Conclusion: Machine learning classifier of radiomic features extracted from Multi parametric MRI images (T1C & T2w) provides important diagnostic information for the non-invasive prediction of the IDH mutant or wild-type phenotype of high-grade gliomas and may have potential use in either escalating or de-escalating adjuvant therapy for gliomas or for using targeted agents in future.